Hyptia deansi sp. nov., the first record of Evaniidae (Hymenoptera) from Mexican amber - Jennings, John T.; Krogmann, Lars; Mew, Steven L. (Zootaxa, 2012)
Hyptia deansi sp. nov. represents the first record of Evaniidae (Hymenoptera) from Lower Miocene to Upper Oligocene Mexi-can amber, Simojovel, Chiapas, Mexico and is described based on a well preserved female specimen. Phylogenetically relevantmorphological characters are discussed with reference to fossil and extant genera of Evaniidae. The new fossil is placed in theextant New World genus Hyptia Illiger 1807, based on the presence of just a single fore wing cell, the absence of tubular veins M+CU, 1CUa, 1Cub, and the presence of 11 flagellomeres.